A comparison of risk factors for mortality from heart failure in Asian and non-Asian populations: An overview of individual participant data from 32 prospective cohorts from the Asia-Pacific Region - Huxley, Rachel; Barzi, F.; Woo, J.; Giles, G.; Lam, T.; Rahimi, K.; Konety, S.; Ohkubo, T.; Jee, S.; Fang, X.; Woodward, M.; Okayama, A.; et al. (2014)
Background: Most of what is known regarding the epidemiology of mortality from heart failure (HF) comes from studies within Western populations with few data available from the Asia-Pacific region where the burden of heart failure is increasing.Methods: Individual level data from 543694 (85% Asian; 36% female) participants from 32 cohorts in the Asia Pacific Cohort Studies Collaboration were included in the analysis. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) for mortality from HF were estimated separately for Asians and non-Asians for a quintet of cardiovascular risk factors: systolic blood pressure, diabetes, body mass index, cigarette smoking and total cholesterol. All analyses were stratified by sex and study.Results: During 3,793,229 person years of follow-up there were 614 HF deaths (80% Asian). The positive associations between elevated blood pressure, obesity, and cigarette smoking were consistent for Asians and non-Asians. There was evidence to indicate that diabetes was a weaker risk factor for death from HF for Asians compared with non-Asians: HR 1.26 (95% CI: 0.74-2.13) versus 3.04 (95% CI 1.76-5.25) respectively; p for interaction = 0.022. Additional adjustment for covariates did not materially change the overall associations. There was no good evidence to indicate that total cholesterol was a risk factor for HF mortality in either population.Conclusions: Most traditional cardiovascular risk factors including elevated blood pressure, obesity and cigarette smoking appear to operate similarly to increase the risk of death from HF in Asians and non-Asians populations alike. © 2014 Huxley et al.; licensee BioMed Central Ltd.